2005
DOI: 10.1016/j.jelechem.2004.07.038
|View full text |Cite
|
Sign up to set email alerts
|

Assembly, electrochemical characterisation and electrocatalytic ability of multilayer films based on [Fe(bpy)3]2+, and the Dawson heteropolyanion, [P2W18O62]6−

Abstract: Abstractimmobilise up to thirty monolayers, with the system exhibiting well behaved redox behaviour. The stability of the assembly towards redox switching was investigated, with it being found be extremely stable once the outer layer is anionic in nature. The 2 immobilised film was also tested for electrocatalytic activity for the reduction of nitrite, hydrogen peroxide and bromate, and was shown to be an efficient electrocatalyst.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
55
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 84 publications
(58 citation statements)
references
References 40 publications
2
55
1
Order By: Relevance
“…It was found that an addition of diethyl ether to the ink suspension caused an increase (approximately by 50 %) of the current densities associated with all the observed redox processes of the CNTs/PDDA/[P 2 This could be ascribed to the formation of the CNT surface groups enhanced or activated by diethyl ether. Our recent studies also showed that an increase of the current intensities was also seen when the ink suspension was prepared using CNTs that had already been modified with PDDA and [P 2 W 17 VO 62 ] 8− .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…It was found that an addition of diethyl ether to the ink suspension caused an increase (approximately by 50 %) of the current densities associated with all the observed redox processes of the CNTs/PDDA/[P 2 This could be ascribed to the formation of the CNT surface groups enhanced or activated by diethyl ether. Our recent studies also showed that an increase of the current intensities was also seen when the ink suspension was prepared using CNTs that had already been modified with PDDA and [P 2 W 17 VO 62 ] 8− .…”
Section: Resultsmentioning
confidence: 99%
“…We found that the investigated system exhibited lower stability in more alkaline media: The percentage losses of activities were up to 30 and 20 % at pH 4.5 and 7.0, respectively. This could be linked to the pH-dependent nature of the polytungstate reduction processes: In alkaline media, availability of protons which are needed to accompany the reductions is obviously lower relative to that in 0.5 mol dm −3 H 2 SO 4 [2].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The probe can undergo the redox transformation at the underlying electrode surface after diffusion through the multilayer system or within the film by electron transfer mediated by the redox sites within the LBL film [28]. …”
Section: Permeability Of Lbl Films Towards Different Redox Probesmentioning
confidence: 99%